Article Review: Phenotypic and Genotypic Identification of Bacillus cereus in Soy Milk - Ni Ketut Sastraningsih; I Putu Bayu Mayura; Ida Bagus Nyoman Putra Dwija (International Journal of Health and Pharmaceutical (IJHP), 2026)
Bacillus cereus  is a Gram-positive, spore-forming bacterium frequently found as a contaminant in various food products, including soy milk, and is recognized as a causative agent of foodborne illnesses. Its pathogenicity mainly arises from the production of toxins such as non-hemolityc enterotoxin (nhe), hemolysin BL (hbl), and cytotoxin K (cytK), which contribute to gastrointestinal disorders. Conventional phenotypic identification methods, including culture, morphological observation, and biochemical assays, are simple but often lack specificity in distinguishing B. cereus from the B. cereus group. Therefore, genotypic approaches based on molecular techniques such as PCR and Whole Genome Sequencing (WGS) are required to achieve higher sensitivity and precision. The gyrB gene serves as a molecular marker for species confirmation, while the nhe gene complex acts as a virulence determinant in identifying toxigenic strains. The integration of phenotypic and genotypic methods provides a more comprehensive understanding of B. cereus contamination in soymilk, elucidating its genetic diversity and pathogenic potential, which are essential aspects of food safety assessment.